Integrasi Manajemen Berbasis Sekolah dan Budaya Lokal: Inovasi Penguatan Lembaga Pendidikan Islam di Kabupaten Bone - Dwiyama, Fajri (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
This article examines the innovation of integrating School-Based Management (SBM) with local culture as a strategy to strengthen Islamic educational institutions in Bone Regency. This study aims to analyze how the values of Bone's local wisdom, such as the principles of